Pathological and physio-biochemical characterization of Xanthomonas axonopodis pv. glycines, incitent of Glycine max leaf pustules - H.N. GOUR, S.K. SAIN* and (Indian Phytopathology, 2013)
The bacterium isolated from soybean (Glycine max L). identified and characterized on the basis of cultural, morphological, pathological and physio-biochemical characteristics as Xanthomonas axonopodis pv. glycines (Nakano) Vauterin,. Hoste, Kersters & Swings. Host-range study showed that the bacterium caused severe disease symptoms on horse gram other than soybean. The fraction of partially purified toxin(s) number 4 and 7 collected by using sephadox gel chromatography were found to be highly toxic to the host plant as well as other plants on detached leaf/twig and seedling (more than 50% wilting). Partially purified toxin treatment caused chlorosis in leaves of turnip, radish, castor, soybean, mustard (> 50%). Toxin treatment also reduced 100% seed germination in clusterbean, gram, coriander, turnip and urdbean. The bacterium produced higher pectinolytic enzyme (83.6%) as compared to cellulolytic and protopectinase enzyme. The loss of viscosity in terms of enzyme activity (50% loss in viscosity) was higher in polyglacturonase (96.1), followed by celllolytic enzymes (54.6), pectin trans- eliminase (50.5), polyglacturonase and polygalacturonate trans-eliminase (49) enzymes. The reduced amount of chlorophyll (a, b and total) 82.9%, carotinoids (20.9%), total nitrogen protein (46.9%) and non-reducing sugars (60.9%) was found in infected plant tissues while reducing sugar and orthodihydroxy phenol had increased. The slight increased activity of peroxidase (25.6%), catalase (22.3%), superoxidase dismutase (36.6%) and ascorbate peroxidase (35.1%) in infected leaf tissues was recorded.